Adverse Pregnancy Conditions Among Privately Insured Women With and Without Congenital Heart Defects. Issue 6 (June 2020) - Downing, Karrie F.; Tepper, Naomi K.; Simeone, Regina M.; Ailes, Elizabeth C.; Gurvitz, Michelle; Boulet, Sheree L.; Honein, Margaret A.; Howards, Penelope P.; Valente, Anne M.; Farr, Sherry L.
Abstract : Background: In women with congenital heart defects (CHD), changes in blood volume, heart rate, respiration, and edema during pregnancy may lead to increased risk of adverse outcomes and conditions. The American Heart Association recommends providers of pregnant women with CHD assess cardiac health and discuss risks and benefits of cardiac-related medications. We described receipt of American Heart Association–recommended cardiac evaluations, filled potentially teratogenic or fetotoxic (Food and Drug Administration pregnancy category D/X) cardiac-related prescriptions, and adverse conditions among pregnant women with CHD compared with those without CHD. Methods and Results: Using 2007 to 2014 US healthcare claims data, we ascertained a retrospective cohort of women with and without CHD aged 15 to 44 years with private insurance covering prescriptions during pregnancy. CHD was defined as ≥1 inpatient code or ≥2 outpatient CHD diagnosis codes >30 days apart documented outside of pregnancy and categorized as severe or nonsevere. Log-linear regression, accounting for multiple pregnancies per woman, generated adjusted prevalence ratios (aPRs) for associations between the presence/severity of CHD and stillbirth, preterm birth, and adverse conditions from the last menstrual period to 90 days postpartum. We identified 2056 women with CHD (2334 pregnancies) and 1 374 982 women without (1 524 077 pregnancies). During the last menstrual period to 90 days postpartum, 56% of women with CHD had comprehensive echocardiograms and, during pregnancy, 4% filled potentially teratogenic or fetotoxic cardiac-related prescriptions. Women with CHD, compared with those without, experienced more adverse conditions overall (aPR, 1.9 [95% CI, 1.7–2.1]) and, specifically, obstetric (aPR, 1.3 [95% CI, 1.2–1.4]) and cardiac conditions (aPR, 10.2 [95% CI, 9.1–11.4]), stillbirth (aPR, 1.6 [95% CI, 1.1–2.4]), and preterm delivery (aPR, 1.6 [95% CI, 1.4–1.8]). More women with severe CHD, compared with nonsevere, experienced adverse conditions overall (aPR, 1.5 [95% CI, 1.2–1.9]). Conclusions: Women with CHD have elevated prevalence of adverse cardiac and obstetric conditions during pregnancy; 4 in 100 used potentially teratogenic or fetotoxic medications, and only half received an American Heart Association–recommended comprehensive echocardiogram. Abstract : Supplemental Digital Content is available in the text.